DEDUCTIVE AND INDUCTIVE APPROACHES TO TEACHING GRAMMAR - Abdukarimova N. A. (International Engineering Journal For Research & Development, 2023)
This article contains information about investigation of effectiveness of teaching English by using deductive and inductive approaches of teaching grammar. The investigation also attempts to see which of these two methods has a positive effect on the grammar academic achievement of the secondary school pupils, so it answers the following questions: What are inductive and deductive approaches of teaching grammar? What advantages and disadvantages they have got? What is the effect of inductive method on grammar achievement compared with deductive method at secondary school? · What is the effect of inductive method on grammar achievement compared with deductive method at secondary school? To answer the questions of the study, the researcher has made research based on inductive and deductive methods for each level based on its syllabus.